EXPLORING THE RELATIONSHIP BETWEEN CONSUMERSâ EMOTIONAL PERCEPTION AND PRODUCT FORMS: A CASE STUDY ON CAR DESIGN - Sutono, Sugoro Bhakti (Universitas Muria Kudus, 2018)
Nowadays, there is a need to analyze the relationship between emotions, consumers and product design need. Hence, the objective of this study is to investigate the relationship between Malaysian consumersâ emotional or feeling preference, or so-called Kansei perception, on product form of car design via survey. A semantic differential method is employed to measure the subjective response of emotional perception. An independent t-test and factor analysis are carried out to analyze the Â consumersâ perception. The consumersâ semantic differential is gathered from a total of 112 subjects, comprising of 56 males and 56 females, whereby the subjects evaluate 12 car designs using 16 Kansei adjective pairs. The results reveal that there no significant differences in perception distribution between males and females for all Kansei impressions. From the factor analysis, it is found that the Kansei impressions on car design can be grouped into three factors which significantly influence the consumersâ emotional perception.